Estimation of the soybean varieties of the world collection according to the trait ‘seed weight per plant’ in the conditions of the central Non-blackearth region - E. V. Gureeva; A. V. Solodyagina (Зерновое хозяйство России)
The purpose of the current study was to estimate the potential of soybean varieties of various ecological and geographical groups according to the trait ‘seed weight per plant’ and to identify varieties with high adaptability to the conditions of the Ryazan region.   The objects of research were 33 soybean samples from the world collection, which differed in morphological and biological characteristics. The soybean variety ‘Sibiriada’ (Russia), zoned for the Central region, was taken as the standard variety. Field trials were carried out on dark gray forest soil at the Institute of Seed production and Agrotechnologies, branch of the Federal Budgetary Scientific Institution “FRAEC VIM”, located in the Ryazan region in 2021–2023. In order to characterize the adaptability parameters, there have been used such indicators as homeostatic index (Hom), coefficient of variation (CV), stability factor (SF); range of the indicator ‘seed weight per plant’ (d), standard deviation (σ); adaptability coefficient (AC); stability level indicator (SLI) and stress resistance (Ymin–Ymax), calculated using appropriate methods. There has been established that according to the trait ‘seed weight per plant’ the varieties ‘Georgiya’, ‘Snezhana’ and ‘Chera 1’ (Russia) had the lowest value of variation with Cv,%≤20.0. It was found that the varieties ‘Georgiya’ and ‘Snezhana’ (Russia) were the most stable to external environmental changes. This was evidenced by the lowest values of the coefficient of variation (Cv = 12.9 and Cv = 14.0 %, respectively) and high homeostaticity (Hom = 31.3 and Hom =28.9). The greatest variability and low homeostaticity were found in the soybean varieties ‘Vereteyka’ (Hom = 1.69, Cv = 58.4 %) and ‘Elena’ (Hom = 2.17, Cv = 50.3 %), which characterized the low adaptability of these varieties to the conditions of the Ryazan region. As a result of the estimation of the genotypes studied in the trial according to the triat ‘seed weight per plant’, it was established that the varieties ‘Georgia’ (Russia), ‘Snezhana’ (Russia), ‘Chera 1’ (Russia), ‘Garmoniya’ (Russia) were of great breeding value for improving adaptability and stability in the forest-steppe agroclimatic zone of the Ryazan region.